THE USE OF MANGA TO TEACH READING NARRATIVE TEXT TO TENTH GRADERS OF SMAN 1 CERME (RETAIN, 2013)
Abstrak Membaca adalah salah satu kemampuan yang memiliki peran penting dalam membangun wawasan siswa. Kemampuan membaca adalah suatu kemampuan untuk mengenali simbol-simbol tertulis dan sebuah proses dari pembaca dalam mengombinasikan informasi dari sebuah teks dan wawasan dasar pembaca dalam membangun arti (Nunan: 1991). Tetapi, hampir semua siswa mengalami kesulitan di dalam kelas membaca bahasa Inggris terutama untuk teks naratif. Pengajaran membaca untuk siswa SMA harus berbeda dengan siswa SD disebabkan oleh perbedaan karakteristik psikologi mereka. Karya ilmiah ini difokuskan pada penggunaan Manga untuk pengajaran membaca teks naratif untuk kelas X SMA. Manga adalah kartun atau novel seri bergambar yang berasal dari Jepang. Manga sangat sesuai dengan teks naratif karena berisi cerita-cerita fiksi. Dalam penerapannya, Guru bahasa Inggris harus memperhatikan level siswa, urutan mengajar dan penyeleksian Manga yang digunakan. Sebagai hasilnya, aspek visual dari Manga dapat membantu para siswa dalam pemahaman membaca teks naratif sekalipun mereka belum pernah membaca Manga. Kata Kunci: Manga, kemampuan membaca, teks naratif Abstract Reading is one of the skills that have an important role in building the students’ knowledge. Reading ability is an ability to recognize printed symbols and a fluent process of reader in combining information from a text and their own background knowledge to build meaning (Nunan: 1991). But, almost the entire students find difficulties in English reading class especially in reading narrative text. Teaching reading for adolescent learners or senior high school students must be different from children in elementary school because of their different characteristic of psychological background. This study focused on the use of Manga to teach reading narrative text to Tenth Graders. Manga is a Japanese style of print cartoon or graphic novel. Manga deals with narrative text because it tells about a story or fiction. In implementing Manga, an English teacher must consider the level of the students, the steps of teaching and also the selection of Manga in implementing this media in the classroom. As a result, the visual aspect of Manga helps to support reading comprehension for all students, even those who are totally unfamiliar with Manga. Keywords: Manga, reading ability, narrative text